Piping systems and pipiline : - Ellenberger, J. Phillip. (McGraw-Hill, 2005)
The Piping Systems & Pipeline Code establishes rules of the design, inspection, maintenance and repair of piping systems and pipelines throughout the world. The objective of the rules is to provide a margin for deterioration in service. Advancements in design and material and the evidence of experience are constantly being added by Addenda. Based on a popular course taught by author and conducted by the ASME, this book will center on the on the practical aspects of piping and pipeline design, integrity, maintenance and repair. This book will cover such topics as: inspection techniques, from the most common (PT, MT, UT, RT, MFL pigs) to most recent (AE, PED, UT pigs and multi pigs), the implementation of integrity management programs, periodic inspections and evaluation of results